Soft-tissue Wound Healing by Anti-advanced Glycation End-products Agents. (April 2014) - Chang, P.-C.; Tsai, S.-C.; Jheng, Y.-H.; Lin, Y.-F.; Chen, C.-C.
The blocking of advanced glycation end-products (AGE) has been shown to reduce diabetic complications and control periodontitis. This study investigated the pattern of palatal wound-healing after graft harvesting under the administration of aminoguanidine (AG), an AGE inhibitor, or N-phenacylthiazolium bromide (PTB), a glycated cross-link breaker. Full-thickness palatal excisional wounds (5.0 x 1.5 mm 2 ) were created in 72 Sprague-Dawley rats. The rats received daily intraperitoneal injections of normal saline (control), AG, or PTB and were euthanized after 4 to 28 days. The wound-healing pattern was assessed by histology, histochemistry for collagen matrix deposition, immunohistochemistry for AGE and the AGE receptor (RAGE), and the expression of RAGE, as well as inflammation- and recovery-associated genes. In the first 14 days following AG or PTB treatments, wound closure, re-epithelialization, and collagen matrix deposition were accelerated, whereas AGE deposition, RAGE-positive cells, and inflammation were reduced. RAGE and tumor necrosis factor-alpha were significantly down-regulated at day 7, and heme oxygenase-1 was persistently down-regulated until day 14. The levels of vascular endothelial growth factor, periostin, type I collagen, and fibronectin were all increased at day 14. In conclusion, anti-AGE agents appeared to facilitate palatal wound-healing by reducing AGE-associated inflammation and promoting the recovery process.